PEMANFAATAN SEVIMA EDLINK DALAM PEMBELAJARAN PAI: STUDI TENTANG FAKTOR PENDUKUNG DAN PENGHAMBAT DI FAKULTAS TARBIYAH IAIN PAREPARE - Sukriadi S; Darmawati Darmawati; Abdul Halik (JITU Jurnal Ilmiah Tarbiyah Umat, 2025)
The development of information technology has brought significant changes to education, including the learning process of Islamic Religious Education (PAI) in higher education. One of the widely used online learning platforms is Sevima Edlink. This study aims to describe the utilization of Sevima Edlink in PAI learning and to analyze the supporting and inhibiting factors of its implementation at the Faculty of Tarbiyah, IAIN Parepare. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving PAI lecturers, students, and system administrators as informants. Data analysis was carried out through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results show that the utilization of Sevima Edlink in PAI learning includes online attendance, distribution of learning materials, discussion forums, assignment submission, and learning evaluation. Supporting factors include institutional policies that support digital learning, ease of application use, and adequate students’ digital literacy. Meanwhile, inhibiting factors consist of limited internet access, technical problems in the application, and the uneven training of lecturers. This study concludes that Sevima Edlink is quite effective in supporting PAI learning, although improvements are still needed in terms of infrastructure and strengthening educators’ digital competencies.